Saffron therapy for the ongoing treatment of age-related macular degeneration - Peter J McCluskey; Thomas Hong; Andrew A Chang; John Grigg; Geoffrey K Broadhead; Timothy E Schlub; Eugenia Chu (BMJ Open Ophthalmology)
Objective To assess the long-term efficacy and safety of oral saffron, a natural antioxidant, in treating mild/moderate age-related macular degeneration (AMD).Methods and analysis Open-label, extension trial of 93 adults (>50 years) with mild/moderate AMD and vision >20/70 Snellen equivalent in at least 1 eye. Exclusion criteria included confounding visual lesions or significant gastrointestinal disease impairing absorption.Participants were given oral saffron supplementation (20 mg/day) for 12 months. Those already consuming Age-Related Eye Diseases Study (AREDS) supplements or equivalent maintained these.Primary outcomes included changes in multifocal electroretinogram (mfERG) response density and latency, and changes in best-corrected visual acuity (BCVA). Secondary outcomes included safety outcomes, changes in mfERG and BCVA among participants on AREDS supplements and changes in microperimetry.Results At 12 months, mean mfERG response density was significantly higher in rings 1, 2 and overall (p<0.001 for all) but not in rings 3–6, and there was no difference in response between those taking AREDS supplements and those not (p>0.05). Mean mfERG latency was not significantly different in any of rings 1–6 or overall (p>0.05 for all), again with no difference between those taking AREDS supplements or not (p>0.05). Mean BCVA was 1.6 letters worse (p<0.05) with no difference between those on AREDS supplements or not, and this may have been related to cataract progression. No saffron-related serious adverse events were detected.Conclusion Saffron supplementation modestly improved mfERG responses in participants with AMD, including those using AREDS supplements. Given the chronic nature of AMD, longer-term supplementation may produce greater benefits.